1995
DOI: 10.1111/j.1440-1789.1995.tb00277.x
|View full text |Cite
|
Sign up to set email alerts
|

Cytopathology of amyotrophic lateral sclerosis: A personal perspective of recent developments

Abstract: Amyotrophic lateral sclerosis (ALS) is an age-associated neurodegenerative disease that primarily involves the motor neuron system. Despite this disease having been studied for over 100 years, its etiology is still unknown and no specific diagnostic laboratory test is available. The diagnosis of ALS is therefore based on clinical and/or neuropathological findings with loss and degeneration of the large anterior horn cells of the spinal cord being the principal and most salient features. Several symposia and wo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
5
0

Year Published

1996
1996
2012
2012

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 36 publications
0
5
0
Order By: Relevance
“…Several studies on ALS have been described for over 100 years [1]. Recent applications of molecular biologi cal techniques to the ALS research suggested that some change of SOD 1 protein may bear relation to a process of this disease [1, 3 -5 , 16-19], However, the patho genic role of SOD1 abnormalities in ALS is still in con troversy.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Several studies on ALS have been described for over 100 years [1]. Recent applications of molecular biologi cal techniques to the ALS research suggested that some change of SOD 1 protein may bear relation to a process of this disease [1, 3 -5 , 16-19], However, the patho genic role of SOD1 abnormalities in ALS is still in con troversy.…”
Section: Discussionmentioning
confidence: 99%
“…Amyotrophic lateral sclerosis (ALS) is an age-depen dent fatal neurodegenerative disorder that mainly involves upper and lower motor neurons [ 1 ]. ALS is subclassified into the sporadic form, the familial form and detoxifies superoxide radical to form hydrogen peroxide and molecular oxygen [II, 12J.…”
Section: Introductionmentioning
confidence: 99%
“…Amyotrophic Lateral Sclerosis is a chronic and invariably fatal disease, characterized by a progressive loss of motor functions and degeneration of motor neurons in the spinal cord, brain stem, and motor cortex [1]. The discovery of mutations in the gene encoding the Cu/Zn superoxide dismutase 1 (SOD1) in certain cases of familial ALS, and the generation of a transgenic mouse model for the disease, provided the hope for understanding the pathogenesis, and developing therapies [2][3][4].…”
Section: Introductionmentioning
confidence: 99%
“…(Am J Pathol 2004, 165:1701-1718) Amyotrophic lateral sclerosis (ALS) is a world-wide, fatal neurodegenerative disease characterized by loss of motor neurons in the cerebral cortex, brain stem, medulla, and spinal cord and by the proliferation of astrocytes. 1 The annual incidence of sporadic ALS in nonendemic areas is 1.0 per 100,000. 2,3 Among the indigenous population of Guam, ALS occurs frequently in combination with parkinsonism and dementia.…”
mentioning
confidence: 99%